MUSIK KATEKETIS : ALTERNATIF MENJADIKAN KATEKESE LEBIH MENARIK. - Aloysius Suhardi (Bahasa Indonesia, 2018)
The main objective of catechism is to motivate the members (of the Church) to fully comprehend their faith and bring their spiritual experiences into reality, both in their religious and social community. The role of the catechism is very important in developing the Catholics in the future. However, the policies of the pastoral council do not put the catechism into the priority. Besides, the motivation of the members in this field is also getting lower. This phenomenon will directly impact the quality of the members' comprehension of their faith during the next decades. There are many ways to activate the catechism. Catechetical music is one means to make the catechism interesting for the members. This article discusses some ideas about the use of music in catechism.